Emotionally intelligent design : rethinking how we create products - Pavliscak, Pamela (Shroff publishers, 2019)
"As technology becomes deeply integrated into every aspect of our lives, we've begun to expect more emotionally intelligent interactions. But smartphones don't know if we're having a bad day, and cars couldn't care less about compassion. Technology is developing more IQ, but it still lacks EQ. In this book, Pamela Pavliscak--design researcher and advisor to Fortune 500 companies--explores new research about emotion, new technology that engages emotion, and new emotional design practices. Drawing on her own research and the latest thinking in psychology, neuroscience, and behavioral economics, Pamela shows you how design can help promote emotional well-being."--Publisher's description.